PENINGKATAN PERDAGANGAN EKSPOR ALAS KAKI INDONESIA DI PASAR CHINA DALAM KERANGKA ASEAN-CHINA FREE TRADE AREA (ACFTA) PADA TAHUN 2014 – 2016 - Gunawan Muhammad Ersyad; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to discuss the increasing of Indonesian footwear export trade in the Chinese market. within the framework of the Asean China Free Trade Area. Indonesia is one of the countries located in the Southeast Asia Region along with nine other countries. Indonesia with ASEAN countries and China in their economies carry out economic activities in the free trade area. In the face of free trade such as the ASEAN China Free Trade Agreement / ACFTA which is effective since January 1, 2010, one strategy to be able to compete is to produce products (goods and services) of quality. Indonesia Wants to Increase the footwear export trade and cooperate with China in facing Asean free trade. The theory used in this study is political economy theory. Neoliberalism is a notion that suggests that human existence can be very profitable and beneficial when we open space for everyone to develop himself through free competition. It can be seen from the steps taken by Indonesia and China is an interdependent cooperation and of course mutual benefit from each other. While in understanding the problem object so that it can produce a hypothesis, this research uses State Level Analysis or state behavior. While in understanding the problem object so that it can produce a hypothesis, this study uses State Level Analysis or state behavior. China is the country that has received the most attention from ASEAN regarding its increasing economic power. This country to be the most strategic choice embraced in economic cooperation. To improve ASEAN trade relations with China, where Indonesia is one of the members that agreed on free trade cooperation within the framework of the ASEAN - China Free Trade Area (ACFTA) agreement. Before the formation of ACFTA, Indonesia's exports experienced a significant decline this is because imported goods have begun to shift domestic goods. Indonesia's footwear industry exports to China experienced a significant increase in filling the supply gap due to a wave of closure of the Footwear factory in China. this is caused by the increasing export demand by China due to the decline in the footwear industry in the bamboo curtain country. Keywords : EXPORT, ACFTA, ASEAN, INDONESIA, CHINA